Influência da utilização do fluido de corte com adição de grafeno na temperatura de usinagem e formação de rebarba no processo de micro fresamento - Cunha, Daniel Fernandes da (2016)
As time passed, humanity needed the development of new materials used in various activities. High strength materials such as titanium and Inconel for example, had been studied because they are widely used for implants in biomedicine, as well as their use in aerospace and automotive industries. Because of its thermal and mechanical properties, these materials are considered difficult to machine, promoting a rapid wear of cutting tools, primarily caused by the high temperatures in machining. With the development of new materials has emerged the need of developing new manufacturing processes. One of today’s innovative processes is the micro-manufacturing. Being a process with a defined cutting tool geometry, burr formation is a constant and undesirable phenomenon formed during the machininig process. Being detrimental to the manufacturing process, overspending deburring operations are constantly employed leading to increase the aggregate cost to the manufactured material. Assembly components are also impaired if there is no control of the burr, with consequences including the disposal of components due to the occurence of this phenomenon. This paper presents the study of micro-milling Inconel 718, investigating influential parameters in the formation of burrs in order to minimize the occurrence of this phenome non. Different feed rates per tooth and cutting speed are evaluated, and different cutting fluids with different methods of applying the fluid. Adding graphene to cutting fluids was considered as a variable to be investigated, which is considered an excellent solid lubricant, in addition to increasing the thermal conductivity of the cooling solution (AZIMI; MOZAF FARI, 2015). The micro-milling temperature was evaluated in the present work. It was observed a new phenomenon that causes the machined surface temperature decreases below room temperature when using the solution water + oil. This phenomenon is explained in further chapters. In order to unravel this phenomenon, a new test was proposed and, from this test, it can be concluded, comparatively, which cutting fluid has a better cooling property.Using cutting fluid with different thermal properties has shown influence when analy zing burr formation and reducing machining temperature.